Sorafenib in Hepatopulmonary Syndrome: A Randomized, Double‐Blind, Placebo‐Controlled Trial. Issue 8 (30th May 2019) - Kawut, Steven M.; Ellenberg, Susan S.; Krowka, Michael J.; Goldberg, David; Vargas, Hugo; Koch, David; Sharkoski, Tiffany; Al‐Naamani, Nadine; Fox, Alyson; Brown, Robert; Levitsky, Joshua; Oh, Jae K.; et al.
Abstract : The tyrosine kinase inhibitor sorafenib improves hepatopulmonary syndrome (HPS) in an experimental model. However, the efficacy and adverse effect profile in patients with HPS are unknown. We aimed to determine the effect of sorafenib on the alveolar‐arterial oxygen gradient (AaPO2 ) at 3 months in patients with HPS. We performed a randomized, double‐blind, placebo‐controlled parallel trial of sorafenib in patients with HPS at 7 centers. A total of 28 patients with HPS were randomized to sorafenib 400 mg by mouth daily or a matching placebo in a 1:1 ratio. We found no statistically significant difference in the median change in AaPO2 from baseline to 12 weeks between the patients allocated to sorafenib (4.5 mm Hg; IQR, –3.8 to 7.0 mm Hg) and those allocated to placebo (–2.4 mm Hg; IQR, –4.8 to 8.2 mm Hg; P = 0.70). There was also no difference between the groups in terms of degree of intrapulmonary shunting by contrast echocardiography. Sorafenib significantly reduced circulating levels of angiogenic markers, including vascular endothelial growth factor receptors ( P < 0.01) and TIE2‐expressing M2 monocytes ( P = 0.03), but it reduced the mental component scores of the Short Form 36 ( P = 0.04), indicating a worse quality of life. In conclusion, sorafenib did not change the AaPO2 or other disease markers at 3 months in patients with HPS. Alternative antiangiogenic therapies or treatments targeting other pathways should be investigated.